2022
DOI: 10.52214/gsjp.v19i.10063
|View full text |Cite
|
Sign up to set email alerts
|

Memory Self-Efficacy and Community Participation

Abstract: Objective: This study examines the relationships between working memory, memory self-efficacy (MSE), and community participation among older adults. Method: 203 United States older adults (age 55+) were recruited through MTurk to complete surveys and a memory task. A multiple linear regression was used to regress MSE and community participation. Main Findings: Entering all variables into the model explained 45% of the variance in community participation (R2 = .45, Adj. R2 = .41, F(7, 141) T = 16.26, p < .00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…It seems that findings of Otsuka and Miyatani's study and of Mashinchi et al's study could complement each other [6,9]. Using bivariate correlations, a previous study examined and found that the relationship between MSE and WM was not significant (r=0.9), which contrasts sharply with the conclusions of Mashinchi et al's research [6,10]. According to the latter, WM and MSE had a noticeable positive correlation.…”
Section: Self-efficacymentioning
confidence: 79%
“…It seems that findings of Otsuka and Miyatani's study and of Mashinchi et al's study could complement each other [6,9]. Using bivariate correlations, a previous study examined and found that the relationship between MSE and WM was not significant (r=0.9), which contrasts sharply with the conclusions of Mashinchi et al's research [6,10]. According to the latter, WM and MSE had a noticeable positive correlation.…”
Section: Self-efficacymentioning
confidence: 79%